Health science students' attitudes towards healthcare teams: A comparison between two universities. Issue 2 (4th March 2018) - Makino, Takatoshi; Lee, Bumsuk; Matsui, Hiroki; Tokita, Yoshiharu; Shinozaki, Hiromitsu; Kanaizumi, Shiomi; Abe, Yumiko; Saitoh, Takayuki; Tozato, Fusae; Igarashi, Ayako; Sato, Mika; Ohtake, Shigeki; et al.
ABSTRACT: There have been few studies comparing the attitudes towards healthcare teams between different universities. This study analysed the differences in attitudes towards healthcare teams between health science students at Gunma University, Japan, which implements a comprehensive interprofessional education (IPE) programme, and Kanazawa University, a similar national university. Study populations were first- and third-year students at the Gunma University School of Health Sciences and the Kanazawa University School of Health Sciences. The present study was performed just after the IPE and multi-professional education subjects at Gunma University in the first term of the 2012 academic year. The first-year students were different cohort from the third-year students. The modified Attitudes Toward Health Care Teams Scale (ATHCTS) was used to measure attitudes towards healthcare teams. The overall mean score on the modified ATHCTS of students at Gunma University was significantly higher than that of those at Kanazawa University. In both first- and third-year students, the regression factor score of "patient-centred care" was significantly higher at Gunma University than at Kanazawa University. Based on the present study, it can be stated that IPE may foster the value of collaborative practice (CP) among health science students.